Relationship between Mother's Knowledge and Family Support with Giving Exclusive Breastfeeding for Children 6-24 Months in the Ogomatanang Village, Lampasio District, Toli-Toli Regency - Aprilia Ningsih, Nikitha; Sakung, Jamaluddin; Moonti, Sriwahyudin (Universitas Muhammadiyah Palu, 2020)
Exclusive breastfeeding is giving breast milk only without giving other food and drinks to babies from birth to six months. In Indonesia, it shows that currently breastfeeding is still a concern, the percentage of infants who are exclusively breastfed for up to 6 months is only 30.2%, of the national breastfeeding target of 80%. This figure is clearly below the WHO target, which requires breastfeeding coverage of up to 50%. One of the areas that are still worrying about exclusive breastfeeding is the village of Ogomatanang. There are still many breastfeeding mothers who do not provide exclusive breastfeeding in Ogomatanang Village. Therefore, the researcher wanted to know the relationship between maternal knowledge and family support with exclusive breastfeeding for children 6-24 months in Ogomatanang Village. The design of this research is analytical research with the Cross-Sectional Study approach. This study used an Accidental sampling technique, with a total sample of 45 respondents. The test used in this research is using the Chi-square test. The results showed that there was no significant relationship between knowledge and exclusive breastfeeding with p-value = 2.31> 0.05. There was a meaningful relationship between family support and exclusive breastfeeding in Ogomatanang Village, Lampasio District, Toli-Toli Regency with p-value = 0.00 <0.05 This study suggests mothers and families in the Ogomatanang Village, Lampasio District, Toli-Toli Regency always to provide exclusive breastfeeding to children 6-24 months of age because breastfeeding is essential for children's growth and development.